Thermal Comfort Assessment in Office under High Air Conditioner Setting Temperature: A Review - Rozmi, Syazana Amni; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2021)
Malaysia is located close to the equator and experience a hot and humid weather throughout the year. The hot outdoor and warm indoor condition has lead the building occupants on relying to the air conditioner to achieve comfort condition. This  practices resulted to energy demand and high carbon emission. Necessary strategies is required to ensure the building occupants use the air-conditioner system efficiently.This study aimed to review the response of building occupants in higher set point temperature and the impact on the productivity. Furthermore, the relationship between comfort temperature with clothing insulation value and wind speed has been analyzed. The method for this review was a systematic review called Preferred Reporting Items for Systematic Review and Meta-Analyse (PRISMA). The first phase was journal identification where journals were collected based on keywords searching. The next phase was screening of journals and several conditions for eligibility and exclusion of journals were set. Data abstraction and analysis took place to compare and analyse data abstracted from the journals. As for the result, it was found that building occupants felt comfortable at 26°C set point temperature. Optimum productivity could be achieved when the preferred condition was “slightly cool” or “neutral”. There are still lack of evidence that high setting air-conditioner temperature can provide thermal comfort especially in long working hour. Meanwhile, it was found that wind speed has stronger relationship with comfort temperature than the clo value with the coefficient of determination (R2) of 0.72. It can be seen that adjusting wind speed was the main priority to achieve thermal comfort among occupants. As a recommendation, thermal comfort among occupants would be achieved in high set point temperature when fan with desired wind speed was implemented and positively affect productivity.